An iterative deferred acceptance mechanism for decentralized, fast and fair childcare assignment - Tobias Reischmann; Thilo Klein; Sven Giegerich (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We design and implement an iterative, program-proposing deferred acceptance mechanism with ties (IDAT) and apply it to childcare assignment in two German cities. The mechanism can accommodate complementarities in providers' preferences, is fast to terminate even in larger cities, is difficult to manipulate in practice, and produces stable allocations. It can be further sped up by introducing two new features. First, allowing for an arbitrary share of facilities who participate in a centralized manner by submitting a rank-order-list over applicants. Second, by breaking ties in applicants' rank-order-lists on a first-come-first-serve basis, which sets incentives for programs to propose faster.
Keywords: C78; D02; D47; D82; I24; 330; Childcare assignment; deferred acceptance algorithm